Accelerometer Implementation as Feedback on 5 Degree of Freedom Arm Robot - Kunal, Kunal; Zuhri Arfianto, Afif; Eko Poetro, Joessianto; Waseel, Farhad; Andri Atmoko, Rachmad (Universitas Muhammadiyah Yogyakarta, 2020)
The research investigated the automatic control system implemented with the 5 DOF (Degree of Freedom) arm robot control system using the closed-loop control method with the MPU 6050 sensor, which integrated the rotation of the MG995 motor servo as a feedback function. The control of this robot used android–based application, in which the app sends data of the rotate angle for each servo motor rotated to a certain angle. The HC – 05 Bluetooth received the data and the Arduino UNO R3 microcontroller processed them. The microcontroller managed every rotation of each servo motor that integrated with an MPU6050 sensor with serial monitor communication to display the rotation of each servo motor. The test results obtained by the standard deviation value showed how large the sample diversity was. The result of this study showed a standard deviation correlation with the number of sample diversity. The higher the standard deviation value, the more sample data spread (data diverse or varies). Otherwise, the smaller the standard deviation value, the more homogenous the sample data. If the standard deviation equals zero, it indicates that the sample has identical data. The highest standard deviation value from servo motor 1 is 5.20, servo motor 2 and 3 are 1.00, servo motor 4 is 2.89, and servo motor 5 is 2.9